Analisis Kejahatan Transnasional: Studi Kasus Penyelundupan Senjata Api Jaringan Filipina Ke Papua - Fathan, Kanzi (Jurnal Sosial Teknologi, 2025)
Indonesia, with its vast expanse of 17,508 islands and a coastline stretching 99,083 km, is highly susceptible to transnational crime. The unique geographic condition of Indonesia as an archipelagic nation with a long maritime boundary makes it fertile ground for transnational criminal groups. Countries undergoing political transitions are also prime targets for these groups. Factors such as weak law enforcement, political uncertainty, and economic crises contribute to the rise of this type of crime. Two cases of firearms smuggling from the Philippines to Papua in May 2014 and November 2020 underscore the urgency of law enforcement and international cooperation in addressing this challenge.The aim of this research is to identify law enforcement efforts and prevention strategies in combating transnational organized crime in Indonesia, particularly those involving firearms smuggling The research method employed is qualitative juridical research. The theoretical framework of this research includes four main approaches: Realism Theory, Neorealism Theory, Human Security Theory, and Criminology Theory. The results of the discussion indicate that firearms smuggling has a significant impact on the security and stability of the country, highlighting the complexity of this global issue. International legal instruments, such as the UN Firearms Protocol, have been established to regulate and combat the illegal arms trade, with the aim of enhancing global security and minimizing its negative impact on peace and stability. This protocol encourages countries to strengthen monitoring and law enforcement regarding the production, import, export, and misuse of firearms. Additionally, other international legal instruments, such as the UN Convention against Transnational Organized Crime and the UN Protocol against the Illicit Trafficking in Firearms, provide a clear framework for combating firearms smuggling. The impact of firearms smuggling is also clarified, particularly on national security, individual security, and international security, with a focus on the protection of human rights and the enforcement of international humanitarian law. Case studies on firearms smuggling networks from the Philippines to Papua emphasize the importance of international cooperation in eradication efforts, with the establishment of PHILINDO PJCM as a concrete step forward.